The Moderating Role of Job Satisfaction in the Effects of Performance Evaluation, Work Facilities, and Job Security on Employee Performance at Bank Mandiri Taspen Branches Throughout the Yogyakarta Region - Sahril Sidik; Rinaldi Rinaldi (Universitas KH. Abdul Chalim Mojokerto, 2026)
Developments in human resource management within the banking sector require organizations to manage factors that can optimally enhance employee performance. However, there remains inconsistency in research findings regarding the role of job satisfaction as a mediating variable in the relationship between organizational factors and employee performance. This study aims to analyze the influence of performance appraisal, work facilities, and job security on employee performance with job satisfaction as a mediating variable at Bank Mandiri Taspen’s Yogyakarta Regional Branch Office. This study employed purposive sampling with 64 respondents who are permanent employees directly involved in banking operations. Data were collected via a four-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.0. The results indicate that performance appraisal, workplace facilities, and workplace safety have a positive and significant effect on job satisfaction, and that job satisfaction has a significant effect on employee performance. The coefficient of determination indicates that the model explains 49.1% of the variation in job satisfaction and 40.2% of the variation in employee performance. These findings confirm that job satisfaction acts as the primary mediating variable in enhancing employee performance.